2013
DOI: 10.1073/pnas.1301895110
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-memory polymer actuators

Abstract: Reading out the temperature-memory of polymers, which is their ability to remember the temperature where they were deformed recently, is thus far unavoidably linked to erasing this memory effect. Here temperature-memory polymer actuators (TMPAs) based on cross-linked copolymer networks exhibiting a broad melting temperature range (ΔT m ) are presented, which are capable of a long-term temperature-memory enabling more than 250 cyclic thermally controlled actuations with almost constant performance. The characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
244
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(248 citation statements)
references
References 23 publications
3
244
1
Order By: Relevance
“…So, the thermally induced reversible bending of active asymmetric layered polymer composites-laminates reported by Basit et al [28] and Imai [29] occurs similarly to the well-known bimetallic strip effect in unconstrained as well as constrained state and under load [28,29]. Westbrook et al [30] described the reversible deformation of free-standing cross-linked polymer system in bending mode, while Behl and coworkers [31,32] as well as Wu et al. [33] reported on reversible deformation of freestanding cross-linked polymer systems in tensile mode caused by internal stresses stored at least in one semi-crystalline phase of the polymer system during its preparation.…”
Section: Two-way Sme In Polymeric Materialsmentioning
confidence: 91%
See 1 more Smart Citation
“…So, the thermally induced reversible bending of active asymmetric layered polymer composites-laminates reported by Basit et al [28] and Imai [29] occurs similarly to the well-known bimetallic strip effect in unconstrained as well as constrained state and under load [28,29]. Westbrook et al [30] described the reversible deformation of free-standing cross-linked polymer system in bending mode, while Behl and coworkers [31,32] as well as Wu et al. [33] reported on reversible deformation of freestanding cross-linked polymer systems in tensile mode caused by internal stresses stored at least in one semi-crystalline phase of the polymer system during its preparation.…”
Section: Two-way Sme In Polymeric Materialsmentioning
confidence: 91%
“…Some current papers [28][29][30][31][32][33] containing results on two-way SME of layered polymer composites consider two other types of thermally induced two-way SME based on quite different physical principles as described above. So, the thermally induced reversible bending of active asymmetric layered polymer composites-laminates reported by Basit et al [28] and Imai [29] occurs similarly to the well-known bimetallic strip effect in unconstrained as well as constrained state and under load [28,29].…”
Section: Two-way Sme In Polymeric Materialsmentioning
confidence: 99%
“…Recently, another strategy was proposed to produce 2W-SM polymers. Behl et al [68] suggested that creation of a special molecular conetwork (skeleton) containing reversible crystallizing/melting segments can overtake the job of external stress. Important prerequisites of this strategy are: presence of nanoscaled crystalline domains which are kept aligned by the skeleton network (thereby overtaking the role of external loading) and a broad melting range of the related crystallites.…”
Section: Two-way Smp (2w-smp)mentioning
confidence: 99%
“…According to the same study, when immersed in water, a two-ply, coiled, silver-plated 180 µm diameter nylon fiber can be electro-thermally actuated at 5 Hz while producing 10% stroke and lifting 22 MPa load. In Reference [63], the focus was to program the SMPs for a sustainable and repeatable operation of bidirectional actuation. They have achieved at least 250 cyclic thermally controlled actuations with almost constant performance.…”
Section: Operation Range Of Smpsmentioning
confidence: 99%